Rice straw insulation sheet - Taemthong, Wannawit (Asia-Pacific Journal of Science and Technology, 2017)
The objective of this research is to produce insulation sheet made from natural materials for walls and ceilings. The natural materials used in this research were java weed, bagasse, and rice straw, while combine materials were clays, gypsum powders, and urea formaldehyde resin. A production of an insulator is made by compressing mixed raw material in a mold with a hydraulic jack. A size of the sheet is 60x60x3 centimeters. An appropriated insulation sheet, found in this research, is made from rice straw and urea formaldehyde resin with a density of 275 kg/m3. Production cost of the sheet is 237 Baht/m2, which is 25% cheaper than the fiber glass insulator. The rice straw insulator is moderately good for using as insulation comparing to the fiber glass. It has a thermal transmittance coefficient of 0.153 W/m•K and can withstand heat for 2.7?C, whereas the fiber glass has thermal transmittance coefficient of 0.197 W/m•K and can withstand heat for 3.6?C by measuring temperature at ceiling of a building under the same conditions.